RISK ANALYSIS OF SHALLOT FARMING IN MALANG REGENCY, INDONESIA - M Zul Mazwan; Jabal Tarik Ibrahim; Wahyu A M Fadlan (Socio-Economics/Agribusiness Department, 2020)
This study was aims to 1) determine the amount of shallot farming income, 2) analyze the risk of production and income of shallot farming. The location of the research was purposively conducted. The type of data is primary data obtained from 80 samples farmers in the study area. Farming analysis was applied to knowing shallot farming income. Furthermore, coefficient of variation (CV) was applied to knowing the risk of production and income. The results showed that R/C ratio as many as 2.11. With that result, it can be said that shallot farming in Malang Regency is feasible. The level of production risk is 37.54% and the level of risk income is 40%. It can be concluded that the risk of production and income of shallot farming during the dry season in Malang Regency is included in the low category.